Social Exclusion, Deprivation and Marginalization of Females of Jammu and Kashmir - lone, Adil majeed (IJRDO- Journal of Educational Research, 2017)
This paper traces the trajectory of women’s socio-economic and educational status in thestate of Jammu and Kashmir. Women constitute almost half of the total human resources(population) of Jammu and Kashmir. Unfortunately, denial of equal socio-economicopportunities and strong traditional bias against women have resulted in low human developmentindices over the years, as Jammu and Kashmir , like many other states, has lagged behind inupgrading the status of half of its women, in many respects. Education is universally accepted asa fundamental agent of socio-economic upliftment but women have not been fairly treated as faras access to education is concerned. It is needless to emphasize that education for women issynonymous to health, information, confidence, dignity, empowerment and independence.Conversely, illiteracy leads to their exploitation in all walks of life. Despite the fact thatwomen’s education in Jammu and Kashmir has been a major area of concern for both thegovernment and civil society and some statistics have changed since independence, though manyground realities have not. Gender bias against women and hence, gender gap still persists inalmost all aspects of women education and we are far behind a condition where ‘educatingwomen’ is no longer a news. The present paper discusses the trail of progress and currenteducational status of women in the state.